Sintesa Biokoagulan dari Chitosan dan Biji Kelor (Moringa Oleifera) untuk Menurunkan Kandungan Senyawa Organik dalam Limbah Cair Tahu - Safitri, Putri Destia; Satriananda, Satriananda; Adriana, Adriana (Jurnal Teknologi, 2024)
Tofu liquid waste contains high organic compounds that potential to pollute water bodies, so it must be treated before being discharged into the environment. This research investigated the processing of tofu liquid waste using natural coagulants Chitosan and Moringa seeds to remove organic compounds in tofu wastewater. The ratio of chitosan to moringa seeds was varied 0:100; 25:75; 50:50; 75:25 and 100:0%. Jar test method has been employed to conduct the experiment, in which the process of fast stirring was 120 rpm for 1-minute, slow stirring was 20 rpm for 20 minutes, and settling time were varied for 1, 2 and 3 hours. The variables measured include Chemical Oxygen Demand (COD), turbidity, pH and Total Disolved Solid (TDS). The best results were obtained at a coagulant ratio of 100:0 with a weight of 1 gram of chitosan and 0 gram of Moringa seeds at a deposition time of 3 hours. Under these conditions the removal of COD reached 71.87%, turbidity removal 81.65%, pH 5.7 and TDS removal 76.32%.